Analisis Dampak Pelatihan dan Pengembangan Sumber Daya Manusia Terhadap Peningkatan Produktivitas Karyawan di Perusahaan - Intan Purnomo; Mudji Kuswinarno (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
In an era of increasingly intense business competition, the quality of human resources (HR) plays an important role in determining the success of the company. This research explores the impact of HR training and development on improving employee productivity as a strategic step to create a competitive advantage. Training is designed to strengthen employees' technical capabilities, while development aims to increase their intellectual and emotional capacity to face future challenges. The research findings show that well-designed training and development programs not only improve skills, but also increase employee motivation, satisfaction and loyalty. This in turn has a positive impact on work productivity and company competitiveness. This research uses a literature study approach by reviewing various literatures to understand the relationship between training, development and productivity. The results are expected to be a reference for companies in designing sustainable HR management strategies.